Petrology - Bogatikov, Oleg A.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
Petrology (Petrologiya) is a journal of magmatic, metamorphic, and experimental petrology, mineralogy, and geochemistry. The journal offers comprehensive information on all multidisciplinary aspects of theoretical, experimental, and applied petrology. By giving special consideration to studies on the petrography of different regions of the former Soviet Union, Petrology provides readers with a unique opportunity to refine their understanding of the geology of the vast territory of the Eurasian continent.
Keywords: Geochemistry; Mineralogy; Geochemistry